Pengaruh Terapi Menulis Pengalaman Emosional Terhadap Penurunan Depresi pada Mahasiswa Tahun Pertama - Theresia Genduk Susilowati; Nida Ul Hasanat (Jurnal Psikologi, 2011)
In the first year, college students will get the stressful events which related to leave parents and friends, also the transition of educational system and new home stay. The stressfulevents can cause negative of cognitive and emotional responses to college students. Therefore, it can cause depression on college student self. This research aims to test the effect writingabout emotional experiences therapy on reducing depression for the first year college students. Research design uses two matched groups design. Subjects (N=12) were divided intoexperimental group (n=6) or control group (n=6). The experimental group was instructed to write about emotional experiences in four writing sessions lasting ± 30 minutes. Outcomeswere measured at pretest, posttest, and follow up by Mixed ANOVA Design. Between Group ANOVA indicated the groups differed significantly on depression (F=25.88, p=.001). WithinGroup ANOVA indicated that experimental group reported significantly reduced depression at pretest, posttest, and follow up (F=33.72, p=.001). Post hoc test revealed that the repeatexperimental group reported significantly reduced depression at pretest-posttest (p=.003), posttest-follow up (p>0,33), and pretest-follow up (p<0,01). This result indicated that writingabout emotional experience therapy can reduce depression for first year college students.